2010
DOI: 10.1016/j.pupt.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 regulates mucin production via ERK phosphorylation

Abstract: Our previous report showed that inhibition of sphingosine kinase (SphK) ameliorates eosinophilic inflammation and mucin production in a mouse asthmatic model. To clarify the role of SphK in airway mucin production, we utilized the mouse asthmatic model and found that both SphK and MUC5AC expression were increased and co-localized in airway epithelium. Next we cultured normal human bronchial epithelial cells in an air-liquid interface and treated with IL-13 to induce their differentiation into goblet cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(3 reference statements)
4
21
0
Order By: Relevance
“…Furthermore, STAT6 siRNA did not decrease IL-13-increased MUC5AC mRNA expression and protein production to baseline levels. These results are consistent with a previous study that indicated that sphingosine kinase 1 regulates IL-13-induced MUC5AC production via extracellular signal-regulated kinase (ERK) phosphorylation, and independent of STAT6 phosphorylation (Kono et al 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, STAT6 siRNA did not decrease IL-13-increased MUC5AC mRNA expression and protein production to baseline levels. These results are consistent with a previous study that indicated that sphingosine kinase 1 regulates IL-13-induced MUC5AC production via extracellular signal-regulated kinase (ERK) phosphorylation, and independent of STAT6 phosphorylation (Kono et al 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that in addition to SPDEF, other pathways may be involved in IL-13-mediated MUC5AC expression. These results were consistent with reports demonstrating that IL-13 induced mucus hypersecretion through mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K) signaling pathways (Atherton et al 2003;Kono et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that doxycycline treatment of NCI-H292-rtTA-CLCA1 cells caused time-dependent activation of 12 MAPKs ( Figure 3A and data not shown). The largest doxycycline-induced increase in MAPK phosphorylation (doxycycline treatment compared with no treatment) was found for MAPK14 ( Figure 3A), consistent with MAPK14 inhibitor blockade of cytok- ine-induced MUC5AC gene expression in airway epithelial cells (12,13,21,26). However, blockade was only achieved at relatively high (10-20 μM) concentrations of inhibitor that may no longer be specific for MAPK14 (27).…”
Section: Clca1 Controls Mucin Gene Expressionsupporting
confidence: 61%
“…The lack of identifiable STAT6-binding sites in the MUC5AC mucin gene promoter indicates that intermediate steps are required to convert the IL-13 signal to mucin gene expression (10,11). In that regard, other studies of cultured human airway epithelial cells have suggested that activation of MEK1/2, PI3K, SPhk1, and MAPK14 (p38α-MAPK) are necessary for IL-13-induced mucus production (12,13). However, these conclusions were typically based on the effects of chemical inhibitors at relatively high concentrations without target validation using genetic tools.…”
Section: Introductionmentioning
confidence: 99%
“…For RNA interference, we used the oligonucleotides (Japan Bio Services, Saitama, Japan) as described previously 30,63 and listed in Supplementary Table S2.…”
Section: Methodsmentioning
confidence: 99%